Health Benefits of Ganoderma lucidum (Reishi) Supplementation for Athletes: A Narrative Review - Szada-Borzyszkowski, Kacper; Owczarenko, Konstancja (Quality in Sport, 2026)
Ganoderma lucidum supplementation has gained increasing popularity over recent decades, with a growing number of health benefits, and therapeutic applications being attributed to this medicinal mushroom. Owing to its rich content of antioxidant, immunomodulatory, and anti-inflammatory compounds, G. lucidum has attracted considerable scientific interest, particularly in the context of cancer prevention and management, as well as cardiovascular health. More recently, these properties have prompted interest in the potential application of G. lucidum supplementation in sport, and exercise settings. The aim of this narrative review is to evaluate the effects of G. lucidum on athletic performance, overall health, and antioxidant status in athletes. The available scientific evidence suggests, that this supplement may possess ergogenic, and health-promoting potential. Several in vitro studies, together with a limited number of human investigations, have reported favourable outcomes, including improvements in maximal oxygen uptake (VO2max), and muscle strength, indicating a potentially beneficial effect of Reishi supplementation. However, the current body of evidence remains limited. Most human studies have relatively small sample sizes, and the available findings are insufficient to support definitive supplementation recommendations. Consequently, further well-designed studies are required before specific guidelines can be established regarding the use of G. lucidum in athletes, or its application within particular sporting disciplines.